Sistem Penghantaran Penghantaran Zat Aktif Analgetik Dan Zat Eksipien Dalam Sediaan Tablet Lepas Lambat - Ananda Kamalia; Fitri Mutiaraning Tyas; Nuria Ludvi Aziz; Rizkya Roswati; Sri Tantia Dinita; Mira Octaviani Malik; Nia Yuniarsih (Universitas Pahlawan Tuanku Tambusai, 2022)
Several tablets with certain active substances need to be made in a sustained release manner, usually in a single dose treatment, if they are not made sustainably or slow release it will reduce the administration of a single dose. Sustained release is the term to identify a drug-driven system designed to achieve a prolonged therapeutic effect by continuing to release the drug for an extended period of time after administration of a single drug dose. The purpose of this journal review is to see how the mechanism of oral drugs in tablet preparations can be made sustainable release. The method used is the application of inclusion and exclusion criteria. Several active substances from the class of analgesic drugs and their excipients have several methods with different concentrations. The influencing factors include the concentration of the active substance and the selection of excipients.